2007
DOI: 10.1002/cne.21539
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of the cadherin family in the developing Drosophila brain

Abstract: The Drosophila genome encodes 17 members of the cadherin family of adhesion molecules, which in vertebrates has been implicated in patterning the nervous system through cell and axon sorting. With only a few exceptions all cadherins show widespread expression in the larval brain. What expression patterns have in common is that 1) they are global, in the sense that all lineages of the central brain or optic lobe, or both, show expression; and 2) expression is stage-specific: some cadherins are expressed only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 100 publications
0
36
1
Order By: Relevance
“…This makes glia a valuable tool to analyze the role of cadherins in cell migration in the nervous system. In contrast to previous reports (Fung et al, 2008;Iwai et al, 1997), we found that N-cad is expressed in peripheral glia and is required for their migration.…”
Section: N-cadherin and Glial Migrationcontrasting
confidence: 99%
See 2 more Smart Citations
“…This makes glia a valuable tool to analyze the role of cadherins in cell migration in the nervous system. In contrast to previous reports (Fung et al, 2008;Iwai et al, 1997), we found that N-cad is expressed in peripheral glia and is required for their migration.…”
Section: N-cadherin and Glial Migrationcontrasting
confidence: 99%
“…The cadherin family of Ca 2+ dependent cell adhesion molecules are primarily involved in homophilic interactions (Arikkath and Reichardt, 2008;Giagtzoglou et al, 2009;Kiryushko et al, 2004) and are required for cell polarity, adhesion and motility (Harris and Tepass, 2010). In the vertebrate and in the Drosophila nervous systems, the most abundant classic cadherin is the neural (N)-cadherin (N-cad) (Fung et al, 2008;Stepniak et al, 2009), which promotes the formation of rather small adherens junctions (AJs) and is thought to provide the mechanical basis for static tissue organization (e.g. defined cell arrangement in polarized epithelium) as well as for plastic connections between cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, Notch loss of function would disrupt cell adhesion and lead to the extrusion of epithelial cells. Subtypes of cadherins, such as DE-Cad, Cad99C, Fat, which we find preferentially expressed in the neuroepithelium (see also Fung et al, 2008), might be activated by Notch to maintain the neuroepithelium, and repressed by L'sc to promote neurogenesis. Notch mutant clones also upregulate expression of the neuroblast transcription factor Dpn (but not of L'sc), and divide asymmetrically only once they have delaminated from the epithelium.…”
Section: Research Articlementioning
confidence: 60%
“…2A,B) (Fung et al, 2008). The Fat pathway modulator lowfat is also expressed in NE (Mao et al, 2009).…”
Section: Expression Of Fat-hippo Pathway Components In the Brainmentioning
confidence: 99%